2012
DOI: 10.1093/her/cys082
|View full text |Cite
|
Sign up to set email alerts
|

'I'm not doing this for me': mothers' accounts of creating smoke-free homes

Abstract: This article explores mothers' narratives of changing home smoking behaviours after participating in an intervention (Reducing Families' Exposure to Smoking in the Home [REFRESH]) aimed at reducing families' exposure to secondhand smoke (SHS) in homes in Scotland. An analysis of qualitative findings illuminates quantitative changes in levels of SHS exposure. Prospective quantitative and qualitative data were drawn from 21 smoking mothers with at least one child under 6 years. Quantitative change was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…Recently, the use of personalized data of the house air quality has been investigated and proven effective in motivating smoking mothers, with small children, to change their smoking behavior with positive impact on the air quality of the house [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of personalized data of the house air quality has been investigated and proven effective in motivating smoking mothers, with small children, to change their smoking behavior with positive impact on the air quality of the house [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Estimates suggest that between 80% and 90% of cigarette smoke is invisible to the human eye 10 and often smokers are unaware of the concentrations of smoke generated by their activity with many considering that opening a window or lighting candles reduces the level of SHS in their home. 11 Previous work from our group has explored the use of air quality information as an educational tool to help motivate smokers to change their smoking behaviour. 12 Smoking mothers, involved in the REFRESH (Reducing Families' Exposure to Second Hand Smoke and Health) study, reported 'shock' at the levels of PM 2.5 measured in their home with some reducing their smoking and/or taking steps to reduce the SHS of their children within the home.…”
Section: Introductionmentioning
confidence: 99%
“…12 Smoking mothers, involved in the REFRESH (Reducing Families' Exposure to Second Hand Smoke and Health) study, reported 'shock' at the levels of PM 2.5 measured in their home with some reducing their smoking and/or taking steps to reduce the SHS of their children within the home. 11 The REFRESH study used the Sidepak AM510 Personal Aerosol Monitors (TSI, Minnesota, USA) to measure and log household PM 2.5 concentrations. 13 The Sidepak device is primarily designed to measure occupational exposures to fine dust and is costly (>£2500), noisy and requires some degree of training to operate: factors that make their use in home-based interventions difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the current study help to build on the results of the REFRESH intervention feasibility study [14, 24], although REFRESH did not offer caregivers NRT, only provided home air quality feedback on two occasions (compared to three in the current study) and the intervention period was significantly shorter (4 vs. 12 weeks). The REFRESH results showed a statistically significant decrease in maximum PM 2.5 between weeks 2 and 4 within the intervention group but no significant difference between the intervention and comparator arm [14].…”
Section: Discussionmentioning
confidence: 91%